2023
DOI: 10.1371/journal.ppat.1011497
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium phytopathogens as insect mutualists

Aileen Berasategui,
Shounak Jagdale,
Hassan Salem

Abstract: As vectors of numerous plant pathogens, herbivorous insects play a key role in the epidemiology of plant disease. But how phytopathogens impact the metabolism, physiology, and fitness of their insect vectors is often unexplored within these tripartite interactions. Here, we examine the diverse symbioses forged between insects and members of the ascomycete fungal genus Fusarium. While Fusarium features numerous plant pathogens that are causal to diseases such as wilts and rots, many of these microbes also engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In addition, Trichoderma , known for various plant beneficial effects, including protection (of plants) from pathogenic microorganisms ( Sharma et al, 2017 ) and disease ( Woo et al, 2023 ), was found to be a dominant fungal genus in Fujian. On the other hand, certain types of Fusaria , a dominant fungal genus identified in the Xinjiang soil samples, are plant pathogens ( Berasategui et al, 2023 ). However, some Fusaria may have beneficial functions, such as organic matter decomposition and nutrient cycling ( Mukjang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Trichoderma , known for various plant beneficial effects, including protection (of plants) from pathogenic microorganisms ( Sharma et al, 2017 ) and disease ( Woo et al, 2023 ), was found to be a dominant fungal genus in Fujian. On the other hand, certain types of Fusaria , a dominant fungal genus identified in the Xinjiang soil samples, are plant pathogens ( Berasategui et al, 2023 ). However, some Fusaria may have beneficial functions, such as organic matter decomposition and nutrient cycling ( Mukjang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, the possible epidemiological role of some insects as occasional vectors of plant pathogenic species must be taken into careful consideration, even if the impact of Cladosporium spp. as plant pathogens is generally lower than other insect-associated fungi such as Fusarium [236].…”
Section: Other Ecological Relationshipsmentioning
confidence: 95%
“…Many insect herbivores are also the vectors of plant diseases, including phytopathogenic fungi. For example, different Fusarium species have been frequently found as the mutualists of beetles and caterpillars, which benefits disease transmission [ 27 ]. The mycobiome analysis of the tortoise beetle Chelymorpha alternans revealed that this insect can be inhabited by Fusarium oxysporum throughout its lifecycle, including the conspicuous coating of beetle pupae by the fungus to confer defense against predators [ 28 ].…”
Section: Competitive Exclusion Among Epf and Between Efp And Other Fu...mentioning
confidence: 99%